Proteomic insights into the combined effects of near-threshold bleaching temperature and prometryn exposure on the coral Galaxea fascicularis - Sichen Li; Yanyu Zhou; Haochen Niu; Weilu Kang; Guowei Fu; Bo Hu; Hongwei Zhao (Marine Environmental Research, 2026)

Enhanced tellurium recovery via ultrasonic-assisted alkaline leaching-electrodeposition with integrated alkali regeneration - Su Yan; Shixing Wang; Libo Zhang; Rong Zhu; Xinrui Yang; Hongliang Liu; Jianqiang Ye; Guowei Luo; Yonggang Zuo; Gengwei Zhang; Guo Lin; Likang Fu (Chemical Engineering Journal, 2026)

Laser-implanted interstitial hydrogen as dynamic electron modulator activates quaternary nanoalloys for ultrahigh HER activity & stability - Guoshuai Fu; Xiaoliang Yuan; Yuexin Xie; Jiling Li; Pu Liu; Guowei Yang (Chemical Engineering Journal, 2026)

Heavier sediment pollution by per- and polyfluoroalkyl substances (PFASs) in tropical coasts compared to temperate regions: An overlooked hotspot - Hui Xie; Shiya Gu; Yang Cui; Jianwei Dong; Hongbing Wang; Guowei Fu (Journal of Environmental Sciences, 2026)

Stratigraphic sequences off NE Hainan Island: Controls on sand resource distribution in the South China Sea - Guowei Fu; Wanli Chen; Shiguo Wu; Siyu Wang; Junjin Chen; Fanchang Zeng; Yue Sun; Xuelin Li (Regional Studies in Marine Science, 2025)

Mid-Holocene sea-level change in the northern South China Sea inferred from coral microatolls: constraints on glacial isostatic adjustment and neotectonic activity - Fei Tan; Guotao Zhang; Guowei Fu; Mingzhuang Wang; Yunfeng Zhang; Qi Shi; Xiyang Zhang; Li Cao; Jian‐xin Zhao; Hongqiang Yang (Quaternary Science Reviews, 2025)

Polychlorinated biphenyl pollution as an unintentional major contaminant in the Pearl River Delta, China - Hongbing Wang; Chenglong Wei; Guowei Fu; Daheng Zhang; Miao Fu; Junyi Jiang; Yue Long; Yanwei Song (Environmental Research, 2025)

Fluorescence-free near-infrared nanoprobes for in vivo resonant Raman imaging - Guowei Fu; Jin Li (Chemical Engineering Journal, 2025)

New insights on desulfurization mechanism of sulfur-containing phases during iron pellet oxidation: Constraints and mitigation strategies - Ke Ma; Jing Yi; Zijian Su; Xiaoguang Bai; Guowei Fu; Tao Jiang; Yuanbo Zhang (Journal of Environmental Chemical Engineering, 2025)

Nuclear Inclusion Protein B-Driven In Vitro Replication System for Potato Virus Y - Jiayu Fu; Zichen Li; Minjun Liu; Guowei Geng (Potato Research, 2025)

Triggering of a 2500-year coral shutdown in northern South China Sea by coupled East Asian Monsoon and El Niño–Southern Oscillation - Fei Tan; Yunfeng Zhang; Guowei Fu; Qi Shi; Xiyang Zhang; Shengnan Zhou; Mingzhuang Wang; Guotao Zhang; Xiaoju Liu; Jian-xin Zhao; Hongqiang Yang (Global and Planetary Change, 2025)

Exploration of microwave absorptivity and catalysis of CMF@Co-MoS2 for microwave-initiated depolymerization of lignin - Yishuai Fu; Wenliang Wang; Hui Miao; Yangyi Cui; Yutong Chen; Ziwei Wang; Guowei Xiao; Bailiang Xue; Weikun Jiang (Chemical Engineering Journal, 2024)

Spatial distribution characteristics, ecological risk assessment, and source analysis of heavy metal(loid)s in surface sediments of the nearshore area of Qionghai - Junyi Jiang; Miao Fu; Jianying Yang; Yanwei Song; Guowei Fu; Hongbing Wang; Cong Lin; Yang Wang (Frontiers in Marine Science, 2024)
To understand the pollution characteristics and potential sources of heavy metal(loid)s in the nearshore sediments of Qionghai, 93 surface sediment samples were collected from the region. The concentrations of 20 elements, including Fe, Mg, Ca, Ti, Mn, Ba, Cr, Sr, Ni, Cu, Zr, As, Hg, Se, Be, Co, Mo, Cd, Ga, and Pb, were measured. The extent of contamination and ecological risk posed by these heavy metals/metalloids were evaluated using the geo-accumulation index, potential ecological risk index, and Nemerow comprehensive risk index. Additionally, correlation analysis, principal component analysis (PCA), and positive matrix factorization (PMF) were employed to identify the potential sources of these elements in the sediments. The findings reveal the following: (1) The mean concentrations of Fe, Ca, Mg, Ti, Cu, Sr, Zr, Mo, Cd, Pb, Hg, As, and Se exceed the background values for shallow sea sediments in China. Notably, Ca, Ti, Sr, Zr, Mo, Hg, and As exhibit coefficients of variation greater than 51%, indicating significant spatial variability primarily driven by anthropogenic activities. (2) The ecological risk assessment identifies Sr, Hg, and As as the principal pollutants and key potential ecological risk factors in the study area, necessitating prioritization in subsequent monitoring efforts. (3) Correlation and source analysis suggest that As and Mn primarily originate from agricultural activities, Sr, Ca, and Mg from aquaculture, Zr, Ti, Mo, Se, Pb, Be, Co, Cu, Ga, Ni, Fe, and Cd from natural sources, and Hg, Ba, and Cr from transportation sources. Additionally, this study identified Sr, Hg, and As as the primary pollutants in the Qionghai nearshore area, with sources predominantly linked to agriculture, aquaculture, and traffic. Regular monitoring will help track the effectiveness of implemented control measures and provide data for ongoing risk assessments, ensuring the protection and sustainability of the marine environment.

Research on comprehensive assessment of coastal erosion intensity based on multi index method - Guowei Fu; Mingguang He; Xiaofeng Chen; Miao Fu; Yanwei Song; Chenglong Wei; Hongbing Wang; Daheng Zhang (Frontiers in Marine Science, 2024)
The intensity of coastal erosion is a measure of the strength of erosion processes affecting coastal areas. Traditionally, assessments of coastal erosion intensity have relied on singular indices, such as the rate of shoreline retreat or erosion, often prioritizing higher rates over lower ones. This approach, however, lacks comprehensive consideration and scientific rigor. In this study, we adopt a more holistic approach by examining the Qionghai-Wanning coast on the eastern side of Hainan Island. We selected four indices that reflect local conditions and influence coastal erosion strength: Annual rate of shoreline change (T1), Beach annual down-cutting rate (T2), Beach slope (T3), Average particle size of the beach (T4). These indices were used to comprehensively evaluate the erosion intensity of the Qionghai-Wanning coast. The evaluation results categorized the study area into six grades: serious erosion (3.45%), strong erosion (6.90%), erosion (20.69%), micro erosion (44.38%), stabilization (20.69%), and accretion (3.45%). The findings indicate that, under the broader environmental trends of global warming and rising sea levels, most sandy coasts exhibit micro-erosion intensity. Areas experiencing strong and serious erosion are predominantly influenced by human activities, such as those occurring in promenade bays, artificial islands, and harbors. To further understand the relationship between these factors and erosion intensity, we employed the Spearman correlation coefficient method. The analysis revealed that the T1 and the T2 are the primary factors influencing coastal erosion intensity, with the T4 serving as a secondary factor. These factors collectively impact the force and energy absorption of the coast through wave and tidal actions, ultimately determining the intensity of coastal erosion. The multi-index assessment method for coastal erosion intensity demonstrated an accuracy of 82.75%, providing a scientific basis for the management, protection, and restoration of coastal areas.

Morphology and evolution of submarine canyons around the Zhongsha Platform, South China Sea: Implications for sedimentary processes in a modern isolated carbonate setting - Junjin Chen; Shiguo Wu; Qi Li; Chenglong Wei; Guowei Fu; Wanli Chen; Yongpeng Qin; Umair Khan; Songlin Wu (Marine Geology, 2024)

Assessment of the community status of seagrass bed and its relationship with environmental characteristics in Wenchang, Hainan Island, China - Miao Fu; Junyi Jiang; Dacheng Wang; Guowei Fu; Yanwei Song; Hongbing Wang; Daheng Zhang (Frontiers in Marine Science, 2024)
As one of the typical coastal ecosystems, seagrass bed has important ecological service functions. In order to enrich the basic data of multispecies tropical seagrass beds, the main controlling factors affecting the community status of seagrass were identified. In this study, the species, distribution and community characteristics of seagrass in Wenchang were investigated at five stations in 2023, and Spearman correlation analysis and Redundancy analysis were used to investigate the relationship between seagrass and environmental characteristics. The results showed that there were 7 species of seagrass belonging to 5 genera in 2 families along Wenchang coast, including Enhalus acoroides , Thalassia hemprichii , Cymodocea rotundata , Cymodocea serrulata , Halophila ovalis , Halophila minor and Halodule uninervis . The distribution of seagrass beds in Wenchang showed an obvious trend of degradation. Except for the relatively stable of seagrass beds in the central part of Wenchang, the seagrass beds on both the north and south sides decreased significantly, and the coverage of seagrass beds decreased from 24.31% in 2016 to 21.0% in 2020, and further decreased to 20.67% in 2023. The data showed that the coverage and aboveground biomass of seagrass were significantly positively correlated with temperature, and the density of seagrass was significantly positively correlated with DO, but significantly negatively correlated with COD. In addition, increased nutrient salts in the water column could negatively affect seagrass bed. In order to promote the sustainable development of seagrass ecosystem and enhance the stability of seagrass habitat, it is suggested to rationally plan the aquaculture scale of the surrounding area; flexibly manage the rake snail, rake clam and other fishing activities, appropriately reduce the frequency of mining; and scientifically plan marine engineering to reduce the damage to seagrass bed.

Ratiometric fluorescence platform for the ultrasensitive detection of kanamycin based on split aptamer co-recognition triggers Mg2+-DNAzyme-driven DNA walker systems - Xia Lu; Long Wang; Guowei Li; Yuxin Wang; Guo Hao; Yi Ding; Mengjia Liu; Shangchen Fu; Liqing Xu; Na Ge; Wupeng Ge (Science of The Total Environment, 2024)

CXCL1/IGHG1 signaling enhances crosstalk between tumor cells and tumor-associated macrophages to promote MC-LR-induced colorectal cancer progression - Lingqiao Wang; Weiyan Chen; Huidong Jin; Yao Tan; Chengwei Guo; Wenjuan Fu; Zhiling Wu; Ke Cui; Yiqi Wang; Zhiqun Qiu; Guowei Zhang; Wenbin Liu; et al. (Environmental Pollution, 2024)

Distribution Characteristics and Factors Controlling Different Phosphorus Fractions in the Soils and Sediments of an Inland Lagoon - Kun Yuan; Rui Wang; Bo He; Guowei Fu; Yanwei Song; Lixin Pei; Shichao Fan; Fangyi Gao (Journal of Marine Science and Engineering, 2024)
Lagoons, significant coastal wetlands, stand out for their vital role in the cycles and transformations of phosphorus. However, the relationship between the spatial distributions of various phosphorus forms in the soil and sediments of lagoon areas remains unclear. This study investigated the phosphorus fractions and distribution patterns in the soil and sediments from Shimei Inland Sea, Hainan Province, China, and identified the factors controlling phosphorus distribution and its relationship with lagoon eutrophication. The results revealed significant enrichment of inorganic phosphorus (IP) in the Shimei Inland Sea (64.1–679.0 mg/kg) and offshore areas (56–627.2 mg/kg), while organic phosphorus (OP) was relatively concentrated in land (60–744.3 mg/kg), suggesting that the productivity of the terrestrial ecosystem controlled the OP content and IP formed from the mineralization of OP was more likely to leach into the water and combine with minerals. Total phosphorus (TP) content was negatively affected by pH, and organic matter, cation exchange capacity and iron/aluminum oxides showed significant positive correlations with TP content. These findings highlighted the coupled impact of soil and sediment physicochemical properties on phosphorus enrichment and transformation, providing theoretical support for the ecological restoration of ecosystems in tropical coastal wetlands.

Molecularly imprinted electrochemical sensor based on metal-covalent organic framework for specifically recognizing norfloxacin from unpretreated milk - Yuchun Fu; Yang Xie; Haizhu Shi; Guowei Zhang; Huaju Zhang; Shun Feng (Food Chemistry, 2023)

Determination of nitrogen sources and losses in surface runoff from different lands at a watershed scale - Zanfang Jin; Jiazheng Xiao; Hongyu Ye; Guowei Fu; Guangyao Li; Wangbin Wu; Feili Li (Environmental Science and Pollution Research, 2023)

Characteristics and evaluation of coastal erosion vulnerability of typical coast on Hainan Island - GuoWei Fu; Chao Cao; KaiZhe Fu; YanWei Song; Kun Yuan; XiaoMing Wan; ZiAng Zhu; ZhaoFan Wang; ZanHui Huang (Frontiers in Marine Science, 2022)
Coastal erosion vulnerability assessment is widely used to assess the loss degree of coastal zone caused by erosion, and plays an important role in coastal natural resources protection, planning, management and decision-making. Based on the natural and social characteristics of the east coast of Qiongdong and the coastal erosion vulnerability index (CVI) method, this study selected 8 assessment indicators, such as shoreline change rate (U1). The Delphi method and the entropy weight method were used to calculate the comprehensive index weight, combined with CVI method and geographic information system (GIS) technology, to quantitatively evaluate the temporal and spatial distribution characteristics of typical coastal erosion vulnerability such as coral reefs in the east of Hainan Island. The study area was divided into 5 grades: very low (31%), low (10%), moderate (28%), high (24%) and high vulnerability (7%), and the overall performance was moderate erosion vulnerability. The research showed that the interannual downward rate erosion of beach (U3) and the rate of change of the isobath (U2) of the beach were the main controlling factors affecting the vulnerability of coastal erosion in the study area, and the coastal dynamic factor had a greater impact than the other two factors. As a natural barrier, the coral reefs in the study area had good wave absorption and energy reduction, and the coral reef coasts showed low coastal erosion vulnerability, due to the complex hydrodynamic characteristics, estuary coasts is the most vulnerable areas. The verification results of the ROC-AUC method showed that the accuracy of erosion vulnerability was 68.9%, which provided an important reference for the ecological restoration of tropical coral reef biological coasts and the development and management of the Hainan Qiongdong coastal zone.

Quantifying nitrate sources in a large reservoir for drinking water by using stable isotopes and a Bayesian isotope mixing model - Zanfang Jin; Jiarong Cen; Yuming Hu; Linjun Li; Yasheng Shi; Guowei Fu; Feili Li (Environmental Science and Pollution Research, 2019)